2022
DOI: 10.1021/acsami.1c21452
|View full text |Cite
|
Sign up to set email alerts
|

Electrothermally Assisted Surface Charge Density Gradient Printing to Drive Droplet Transport

Abstract: Surface 2019, surface charge density (SCD) gradient printing-driven droplet transport, has attracted considerable attention as a novel and effective approach, which adopts the water droplet impacting a nonwetting surface to create a reprintable SCD gradient pathway conveniently and realizes the high-velocity and long-distance transport of droplets. In the present work, we further investigated the effects of electrothermal behavior on SCD gradient printing on hydrophobic surfaces by considering the droplet impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 31 publications
(52 reference statements)
0
19
1
Order By: Relevance
“…Furthermore, considering that the SCD is easily affected by environmental humidity, the authors further investigated experimentally the roles of electrothermal behavior on the SCD gradient printing strategy. 34 We found that after activating the electrothermal function, the infiltrated depth of a falling droplet on the superhydrophobic surface was increased to generate a larger solid−liquid contact area. A larger contact area raised the probability of solid−liquid contact electrification and produced a more favorable SCD on the superhydrophobic surface.…”
Section: ■ Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Furthermore, considering that the SCD is easily affected by environmental humidity, the authors further investigated experimentally the roles of electrothermal behavior on the SCD gradient printing strategy. 34 We found that after activating the electrothermal function, the infiltrated depth of a falling droplet on the superhydrophobic surface was increased to generate a larger solid−liquid contact area. A larger contact area raised the probability of solid−liquid contact electrification and produced a more favorable SCD on the superhydrophobic surface.…”
Section: ■ Introductionmentioning
confidence: 86%
“…To study the dynamic transport behavior of water droplets along a superhydrophobic surface with the preprinted SCD gradient, the Navier−Stokes equation should be solved numerically by coupling the electric force, which is different from our previous work. 34 The liquid−gas interface also needs to be captured using the computational fluid dynamics (CFD) tool.…”
Section: ■ Numerical Modelingmentioning
confidence: 99%
See 3 more Smart Citations